Scoping review of stepped care interventions for mental health and substance use service delivery to youth and young adults. Issue 4 (21st May 2021) - Berger, Mai; Fernando, Saranee; Churchill, AnnMarie; Cornish, Peter; Henderson, Joanna; Shah, Jai; Tee, Karen; Salmon, Amy
Abstract: Aims: Many young people with mental health and/or substance use concerns do not have access to timely, appropriate, and effective services. Within this context, stepped care models (SCMs) have emerged as a guiding framework for care delivery, inspiring service innovations across the globe. However, substantial gaps remain in the evidence for SCMs as a strategy to address the current systemic challenges in delivering services for young people. This scoping review aims to identify where these gaps in evidence exist, and the next steps for addressing them. Methods: A scoping review was conducted involving both peer‐reviewed and grey literature. Eligible studies explored SCMs implemented in the various health care settings accessed by young people aged 12–24 seeking treatment for mental health and substance use challenges. After screening titles and abstracts, two reviewers examined full‐text articles and extracted data to create a descriptive summary of the models. Results: Of the 656 studies that were retrieved, 51 studies were included and grouped by study team for a final yield of 43 studies. Almost half of the studies were focused on the adult population (i.e., 18 and over), and most did not specify interventions for young people. Among the SCMs, substantial variability was found in almost every aspect of the models. Conclusions: Considering the current body of evidence, there is an urgent need for a consensus position on the definition, implementation, and outcome measures required for rigorously assessing the utility of SCMs for young people.